Evaluation of the Governance of the National Initiative for Human Development and Its Impact on Territorial Development in Morocco's Eastern Rif from 2005 to 2024: A Case Study of the Oulad Zbair and Beni Frassen Communities - El-Fazziki, Mohamed; Ghmimed, Fatima; El-Bazwi, Jawad; Bouberria, Abdelouahed (Arab Journal for Sciences and Research Publishing, 2024)
This study aims to analyze and evaluate the role of governance in implementing the National Initiative for Human Development projects and their impact on territorial development in Morocco’s eastern Rif region, focusing on the communities of Oulad Zbair and Beni Frassen from 2005 to 2024. The research employs a geographic descriptive methodology to analyze official and field data, assessing the impact of the National Initiative for Human Development in the areas of education, healthcare, and infrastructure. Findings indicate that the initiative has contributed in a limited way to local development, facing challenges related to the multiplicity of stakeholders, project sustainability, and the lack of effective mechanisms for monitoring and oversight. The study highlights an urgent need to improve governance of development programs through enhanced community participation and the development of training programs to ensure project sustainability and effectiveness. It recommends adopting stronger oversight and coordination mechanisms among involved entities to reinforce the initiative’s impact on comprehensive and sustainable development.
Keywords: Governance; National Initiative for Human Development; territorial development; eastern Rif Morocco; development programs; project sustainability